Mapping Hydrometeorological Disaster Hazards of Landslides as an Effort to Build Regional Resilience in Banten Province - Rahman, Fathin Aulia (Universitas Lampung, 2024)
Hydrometeorological disasters are disasters caused by atmospheric dynamics related to water, air, and the earth's surface. The use of spatial data for disaster hazard mapping has not been widely carried out in various regions of Indonesia, especially for specific disasters such as hydrometeorological disasters, including floods, landslides, and droughts. The purpose of this study is to map the hydrometeorological disaster hazards in the form of landslides in Banten. Based on the bibliometric analysis that has been carried out, no research was found that focused on mapping the hydrometeorological disaster hazards of landslides in the Banten Province area. The research method used is spatial analysis using the ArcGIS application and AHP for mapping landslide hazards in Banten Province. The parameters used include slope maps, precipitation, distance to faults, soil types, geology, drainage density, slope direction, and NDVI vegetation density. The results of the analysis show that the area with a high level of danger is the largest, with a coverage of 1929.99 km2, the area with a moderate level of danger is 10007.36 km2, and the area with a low level of danger is the smallest, at 128.13 km2. The preparation of a landslide hydrometeorological disaster hazard map is one of the components that can increase the regional resilience index in Banten.Keywords: Mapping; Hydrometeorology; Landslide; Resilience; Banten